2011
DOI: 10.3113/fai.2011.0380
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Analysis of Wedge Allograft Correction of Angular Malalignment in Ankle Fusion

Abstract: The tibiotalar joint fusion rate in this series compares favorably to historically published data for standard ankle fusion. Interposition allograft was an effective method for deformity correction in difficult ankle arthrodeses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“… 18 Fusion rates in correcting valgus and varus tibiotalar deformities with a femoral head allograft have been comparable with standard ankle fusion rates in previous literature. 19 Although long-term and patient-reported outcomes have not been noted, a recent study reports that using a 3-dimensional custom metal sphere was shown to have a significantly greater fusion rate with a lower graft resorption rate when compared with femoral head allografts in TTC fusion. 20 For cases with large structural bone loss, the cup-and-cone technique previously described serves as a promising procedure to preserve limb length, correct ankle or hindfoot deformities, and achieve fusion in patients undergoing TTC arthrodesis.…”
Section: Discussionmentioning
confidence: 99%
“… 18 Fusion rates in correcting valgus and varus tibiotalar deformities with a femoral head allograft have been comparable with standard ankle fusion rates in previous literature. 19 Although long-term and patient-reported outcomes have not been noted, a recent study reports that using a 3-dimensional custom metal sphere was shown to have a significantly greater fusion rate with a lower graft resorption rate when compared with femoral head allografts in TTC fusion. 20 For cases with large structural bone loss, the cup-and-cone technique previously described serves as a promising procedure to preserve limb length, correct ankle or hindfoot deformities, and achieve fusion in patients undergoing TTC arthrodesis.…”
Section: Discussionmentioning
confidence: 99%
“…16 Some studies with allografts have demonstrated high rates of fusion, albeit with low sample sizes. [37][38][39][40] DeFontes et al 37 described a novel technique implementing talar allografts in a series of 6 patients undergoing TTC arthrodesis and reported no nonunions, though follow-up for some patients was inadequate. In a subgroup of 8 patients with bone loss requiring either a femoral head or proximal humeral allograft in combination with bone morphogenic protein, Lucas Y Hernandez et al 39 reported a 100% fusion rate in both subtalar and ankle joints when using a straight Intramedullary (IM) nail.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in a study investigating ankle arthrodesis with allograft supplementation, 2 of 3 (66.7%) patients achieved complete fusion after TTC arthrodeses using a lateral blade plate. 38 Additionally, in 11 patients undergoing TTC fusion with retrograde IM compression nail and femoral head allografts, 9 (82%) achieved fusion. 40 Consistent with these aforementioned studies, we have demonstrated a rate of complete radiographic union, defined as fusion at the ankle and subtalar joints, of 63%, a partial (1 joint) union rate of 88%, and an overall individual joint fusion rate of 75%.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 ] These adverse biomechanical conditions lead to abnormal gait patterns and to increased hindfoot symptoms. [ 1 , 4 , 6 , 9 11 ]…”
Section: Introductionmentioning
confidence: 99%